Coping with the Challenges of Open Online Education in Chinese Societies in the Mobile Era: NTHU OCW as a Case Study - Young, Shelley Shwu-Ching; Hung, Hui-Chun (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
In an era witnessing the rapid development of information technology, mobile devices have brought revolutionary changes to learning. A single conventional media platform is not enough for the various mobile devices. Technology-enriched educational environments supported by different devices are important research issues nowadays. To capture the rapid growth of mobile users in Chinese societies, OpenCourseWare (OCW) needs to move their learning models toward the mobile sphere. Therefore, this study reports the three years of empirical experience in implementing the upgraded National Tsing Hua University OCW platform and analyzes how users access the platform with various devices. The results indicate a responsive web design and cloud-computing provide great accessibility to meet the diversity of various mobile devices from Chinese users throughout the world, including 466,429 visits with 264 different mobile devices from 146 territories. Moreover, the proposed solutions make the workflow of OCW production more efficient. The study further discussed the importance of both tablets and smartphones. Moreover, to expand the reach of open educational resources (OER) in Chinese societies, the critical issues of fair use and sustainability of OER should be of concern. The findings of the study provide valuable references for web engineers and educators to explore cross-device online learning using PCs and mobile devices.